Role of Salivary Biomarkers in Predicting Orthodontic Tooth Movement Rate and Root Resorption. A clinical study: Salivary Biomarkers in Orthodontic Tooth Movement - ABID, JAWERIA; MARYAM, IMSHA; GULZAR, MARYAM; QASIM, SHAZIA (Pakistan Journal of Medical & Health Sciences, 2025)
Background: Orthodontic tooth movement (OTM) is a complicated biological process consisting of inflammation, bone resorption and formation in the periodontal ligament. In the recent past, salivary biomarkers have been invited as being non-invasive measures of biological activity during orthodontic procedures. This was a clinical research agenda to determine the predictive capacity of the chosen salivary biomarkers regarding the speed of movement of teeth and the level of root resorption. Methods: 100 orthodontic patients (between 12 and 25 years old) were subjected to a prospective clinical trial in the retraction of bilateral maxillary cusps. The measures of unstimulated saliva were taken at baseline and 24 hrs, 7 days, 28 days and 8 weeks after activation. They were measured using ELISA IL-1-EB-IL-6, IL-1-EB-RANKL, IL-1-EB-OPG, IL-1-EB-ALP, MMP-8, MMP-9, DSP and TRAP-5b. Tooth movement was assessed in 3D intraoral scan and digital calipers whereas root resorption was assessed through radiograph. Rating on correlation and regression were employed to identify the predictive associations amidst biomarkers and clinical outcomes. Results: IL-1b, IL-6, RANKL, MMP-8, and MMP-9 increased significantly with time, and correspondingly, classifying as decrease with time in OPG (p < 0.001). The tooth movement rate had strong positive associations with the RANKL/OPG ratio and the ALP activity (r = 0.52 and r = 0.45). The level of root resorption was related to high levels of DSP and MMP-9 (p < 0.01). The study did not demonstrate any noticeable periodontal inflammation or systemic confounders. Conclusion: Salivary biomarkers especially the RANKL/OPG ratio, IL -1B, MMP-9 and DSP are stable non-invasive biological activity measures during orthodontic treatment. Their tracking would allow one to anticipate the individual tooth movement rates and identify early root resorption which would allow to implement the biologically informed and patient-centered methods of orthodontic treatment.